Anna, Banana, and the recipe for disaster - Rissi, Anica Mrose (Rissi, Anica Mrose. Anna, Banana, 2018)
"Anna must whip up a new cookie recipe for the bake sale when her jealousy of Sadie and Isabel's new friend has her exaggerating her baking skills"--